An Advanced Class of Bio-Hybrid Materials: Bionanocomposites of Inorganic Clays and Organic Stereocomplex Polylactides - Purnama, Purba; Jung, Youngmee; Kim, Soo Hyun (WILEY-V C H VERLAG GMBH, 2013)
Bio-stereo nanocomposite polylactides are prepared by polymerization followed by stereocomplexation in scCO2/dichloromethane through in situ polymerization and master batch processes. The bio-stereo nanocomposite polylactides show intercalated-exfoliated and fully exfoliated nanoscale clay distribution in a perfect stereocomplex polylactide matrix. In situ polymerization proves better strategy to produce well-exfoliated silicate layers in the stereocomplex matrix compared to the MB route that increases the melting temperature by up to approximate to 64 degrees C. The thermal properties of these materials maintain both stereocomplex and nanocomposite features simultaneously. The results open a new and versatile way to develop polylactide-based materials.
Keywords: ENANTIOMERIC POLY(LACTIC ACID)S; SITU INTERCALATIVE POLYMERIZATION; SILICATE NANOCOMPOSITES; POLY(D-LACTIC ACID); LEUPROLIDE; PROPERTY; BLENDS; FILMS; PLA